POTENSI ANTIMALARIA EKTRAK DIKLOROMETAN DAUN BUNGA MATAHARI (Helianthus annuus L.) SECARA IN VIVO PADA HEWAN COBA - Roihatul Muti’ah; Elok K.H; Ijro’atu Ijro’atu (SAINSTIS, 2012)
Antimalaria experiment on this research aimed to know the activity of extract sunflower leaf to the growth of parasit Plasmodium berghei   in mice balb/c. Mice is being infected by interaperitonial with 106 Plasmodium berghei and divided into 5 groups of treatment, they are (1) positive control, (2) artemisin control 0,004 mg/g BB, , (3) extract sunflower of dose 1 (0,05 mg/g BB), (4) extract sunflower of dose 2 (0,5 mg/g BB) and extract sunflower of dose 3 (5 mg/g BB). Those experiment of antimalaria activity used Peter method. The therapy is done when degree of parasitemia after infected reach 5-15% that was counted as day -0 and it is given during 5 days. Monitoring the degree of parasitemia is done in day -0, day -1, day -2, day -3, and day -5. The result shows that all dose of extract diklorometan sunflower can kill parasit plasmodium berghei and degree of parasitemia reached 0% in day -3 and day -4 after therapy. The statistic analysis shows that the first, second, and third doses on the positive control group have siginificant differences with p 0.05. on the artemism group, first, second, and third doses doesn’t show significant differences with p 0.05. This shows that extract diklorometan having high potential as antimalaria and the effect is the same with artemism.